Editorial The Making of a Neurologist: The Making of a Neurologist (Bombay Hospital Journal, 2021)
“Papa, all is well, I am settled in my new hostel and Iam going to join my Neurology unit today, wish me luck!”Aditya made an early morning call as he was getting ready tojoin the new Neurology posting. Of course, his parents weredelighted, and he had struggled so much to get admission tothis prestigious course. Neurologists are so few in the country,only a few thousand for such a large population, and theirson was entering such a respected specialty of medicine. The“brain doctor” holds a special place in the rank and file ofmedical professionals as he deals with the most complicatedand perhaps most evolved organ in the human body